(untitled) (Web of Teachers: Inderscience Research, 2024)
Organic chemistry is a complex subject that often poses challenges to both educators and learners due to its abstract concepts and three-dimensional structures. The emergence of virtual reality (VR) and augmented reality (AR) technologies presents new opportunities to enhance the teaching and learning experience in organic chemistry. This research paper explores the advantages of using VR and AR technology in teaching organic chemistry, including improved visualization, interactive learning, and enhanced student engagement. Additionally, it examines the potential of these technologies to bridge the gap between theoretical knowledge and practical application, ultimately improving students’ understanding and retention of organic chemistry concepts.